Sustainable e-Governance and Human Resource Development - Burlacu, Sorin; Alpopi, Cristina; Mitrită, Marcela; Popescu, Maria-Loredana (European Journal of Sustainable Development, 2019)
Much of the literature focusing on organizational change suggests that changes often fail because of employees’ resistance. This resistance is caused by their personal fears that change will affect them in any way. Employees are often afraid of changes that could lead to changes in comfortable social dynamics and to additional, less desirable or even more difficult tasks. The proliferation of new technologies brings new challenges but also concerns about job stability. Our paper addresses the issue of human resources development from e-government perspective and presents some features that could be considered when promoting technologies especially in sensitive areas such as public administration. The methodology of research aimed at measuring and interpreting a set of economic, technical and social aspects present in public organizations in Romania. The research findings show how HR is transforming into the digital era and what one might consider to bridge the gap between knowing and doing what is needed to put technology together with the latest processes and skills for a sustainable development of human resources. Keyword: e-HR, the digital era, the development of human resources